Governing AI in Management Accounting: Evidence from an Emerging Industrial Economy - Martius Martius; M. Iqbal Yusuf Conoras; Desti Asfina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The increasing use of artificial intelligence (AI) in management accounting offers significant potential for improving information quality while simultaneously raising concerns about accountability and managerial decision discipline, particularly in emerging industrial contexts. This study aims to explore in depth how AI governance is practiced within management accounting systems and how management control mechanisms frame AI use to support accountability and organizational value creation. The study draws on the literature on management accounting digitalization, AI governance, and management control theory. A qualitative case study approach was employed in the Batam industrial area, using semi-structured interviews, internal document analysis, and limited observation, with data analyzed through thematic analysis. The findings indicate that AI is predominantly positioned as decision support rather than a decision driver, enhancing managerial sensemaking while preserving human judgment through decision ownership, review routines, and documentation. These results suggest that the value of AI in management accounting depends less on technological sophistication and more on the maturity of governance and control mechanisms that ensure disciplined and accountable decision-making.